Problem-based training improves recognition of patient hazards by advanced medical students during chart review: a randomized controlled crossover study. - Friederike Holderried; Daniel Heine; Robert Wagner; Moritz Mahling; Yelena Fenik; Anne Herrmann-Werner; Reimer Riessen; Peter Weyrich; Stephan Zipfel; Nora Celebi (PLoS ONE, 2014)
Background Patient chart review is the gold standard for detection of potential patient hazards (i.e. medication errors or failure to follow up actionable results) in both routine clinical care and patient safety research. However, advanced medical students' ability to read patient charts and to identify patient hazards is rather poor. We therefore investigated whether it is possible to teach advanced medical students how to identify patient hazards independent of context (i.e. cancer versus cardiac failure) in patient charts. Methods All fifth-year medical students in one semester (n = 123) were randomized into two groups. One group (IC) received a patient chart review-training first and then a control-intervention and the other group (CI) received the control-intervention first and then the patient chart review-training. Before and after the teaching sessions, students reviewed different scenarios with standardized fictional patient charts containing 12 common patient hazards. Two blinded raters rated the students' notes for any patient hazard addressed in the notes using a checklist. The students were blinded to the study question and design. There was no external funding and no harm for the participating students. Results A total of 35 data sets had to be excluded because of missing data. Overall, the students identified 17% (IQR 8-29%) of the patient hazards before the training and 56% (IQR 41-66%) of the patient hazards after the training. At the second assessment students identified more patient hazards than at the first. They identified even more in the third. The effect was most pronounced after the patient chart review training (all p<.01). Conclusion Patient chart review exercises and problem-based patient chart review training improve students' abilities to recognize patient hazards independent of context during patient chart review.